Occupational Safety Risk Assessment of Chemical Mixing Process at PT Jabil Circuit Indonesia Using Hazard and Operability Study - Parapat, Riny Yolandha; Rizky, Aldi Muhamad; Septiyaningsih, Nisa Wahyu (Jurnal Penelitian Inovatif, 2026)
The chemical mixing process in the electronics industry has a high potential hazard, particularly due to the use of hazardous substances such as chromium trioxide and chromic acid-based compounds, which are toxic, corrosive, and reactive. This study aims to analyze occupational health and safety risks in the chemical mixing process at PT Jabil Circuit using the Hazard and Operability Study method. The research method was carried out by identifying process deviations based on operational parameters such as flow rate, temperature, concentration, and agitation system in the mixing tank unit. The analysis was conducted using guide words to determine causes, consequences, and risk control recommendations. The results indicate that the main risks occur in temperature and concentration deviations, which can increase reactivity, release hazardous vapors, and expose workers to toxic substances. In addition, the manual process increases the potential for human error during chemical addition. Therefore, risk control measures through engineering controls, administrative controls, and the use of personal protective equipment are required to minimize workplace accidents. The Hazard and Operability Study method is proven effective in identifying and evaluating risks in chemical mixing processes.